The Influence of Social Media Marketing on Purchase Decisions Mediated by Brand Awareness (Study on Sekumpulan Coffee Samarinda) - Sem, Nainggolan Mario; Anny Nurbasari, Anny (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
Researchers are interested in discussing the title "The Influence of Social Media Marketing on Purchase Decisions Mediated by Brand Awareness (Study on a Sekumpul Kopi Samarinda)" Research is intended to be able to see the effect in the form of Structural Equation Modeling (SEM) using SmartPLS. The population in this study is the Samarinda community. The sample in this Research is the consumers of the Samarinda Coffee Group. Data collection was carried out by survey using a questionnaire instrument, with data processing methods such as structural equation modelling (SEM) using SmartPLS to test the hypothesis. The result shows the Influence of Social media marketing on Purchase Decisions mediated by Brand Awareness. Thus, it is necessary to carry out various activities that can encourage consumers to be aware, for example, by conducting education about coffee and increasing awareness among the public.